PINJAMAN ONLINE DAN KERENTANAN KELUARGA MUSLIM PRESPEKTIF MAQASHID SYARIAH - Eva Fadhilah; Sri Agustina (Syaksia: Jurnal Hukum Perdata Islam, 2026)
The development of online lending (pinjaman online or pinjol) services has provided easier access to financing for the public. However, on the other hand, it has also generated various challenges that have the potential to threaten family resilience. This study aims to analyze the impact of online lending on family vulnerability from the perspective of maqāṣid al-syarī‘ah and to formulate strategies for strengthening family resilience amid the growing use of digital financial services. By implementing a conceptual approach and descriptive analysis based on the maqāṣid al-syarī‘ah framework, the study finds that although online lending may offer benefits as an alternative source of financing, from an Islamic legal perspective it is considered prohibited (haram) due to the presence of riba (usury). Furthermore, online lending may give rise to various forms of family vulnerability, including economic vulnerability, psychological vulnerability, and relational vulnerability, which may ultimately lead to divorce and even loss of life. These vulnerabilities indicate potential threats to the objectives of maqāṣid al-syarī‘ah, particularly in safeguarding wealth, life, intellect, and family. Therefore, strengthening family resilience requires synergy among more effective regulatory frameworks, enhanced financial literacy, and the reinforcement of family functions through authoritative-democratic relationship patterns. Such measures are essential to mitigate the negative impacts of online lending and to promote the well-being and sustainability of Muslim families in the digital era.